Analogy-Based Selective Problem-Solving Learning on the Skill to Solve Word Problems - Isna Fauziyah Nurroini; Mohammad Faizal Amir; Mahardika Darmawan Kusuma Wardana (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
Researchers generally use SPS learning to develop creative thinking and problem-solving through analogical thinking. While the problem-solving word problems of elementary school students still need a lot of attention. This study aims to determine the application of analogy-based particular problem-solving (SPS) learning to improve students' problem-solving in word problems. The research method used is a quantitative experimental approach regarding the ability to solve students' math problems before and after being given treatment in the form of SPS learning. The test is given to students through a mathematical word problems solving instrument. Students' problem-solving abilities are measured based on the steps of solving problems, according to Polya. The subjects of this study were fifth-grade students at SDN 188 Gresik. Data collection techniques using tests. Meanwhile, data analysis using the t-test. The results of the SPS on problem-solving skills obtained t-table > t-count, namely 4.102 > 2.0930. The results showed that analogy-based SPS learning impacted elementary school student's ability to solve math problems in word problems. The results of this study imply that elementary school teachers can use analogy-based SPS in cultivating concept-oriented understanding and leading to students' problem-solving abilities.